DIGITAL TRANSFORMATION AND HUMAN RESOURCES READINESS: A STRATEGIC CONCEPT HIGHER EDUCATION VALUE - Nurul - Hidayati (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2022)
The readiness and availability of superior Human Resources (HR) is an important aspect in accelerating development. As an effort to improve the quality of human resources, universities need to be encouraged to prepare an ecosystem that is relevant to the times. In order to be able to play a role in the industrial revolution 4.0, it is necessary to prioritize efficient technology and increase human resource competencies in accordance with the needs in the industrial era 4.0. The availability of technology, support for competent human resources in models and designs within the framework of the technology ecosystem are important and are challenges as well as opportunities for universities to reach the level of the industrial revolution 4.0. The readiness of universities to respond to changes can increase competitiveness so that they can play a role and benefit from the industrial revolution 4.0. This article proposes an approach based on the assessment of the digital transformation readiness of higher education institutions on the following aspects: 1) assessment of higher education architecture; 2) information and technology infrastructure; 3) process management; 4) the potential of human resources; and 5) financial instruments